COVID-19 vaccination and Atypical hemolytic uremic syndrome - Bouwmeester, Romy N.; Bormans, Esther M.G.; Duineveld, Caroline; van Zuilen, Arjan D.; van de Logt, Anne-Els; Wetzels, Jack F.M.; van de Kar, Nicole C.A.J. (Frontiers in Immunology, 2022)
Introduction COVID-19 vaccination has been associated with rare but severe complications characterized by thrombosis and thrombocytopenia. Methods and Results Here we present three patients who developed de novo or relapse atypical hemolytic uremic syndrome (aHUS) in native kidneys, a median of 3 days (range 2-15) after mRNA-based (Pfizer/BioNTech’s, BNT162b2) or adenoviral (AstraZeneca, ChAdOx1 nCoV-19) COVID-19 vaccination. All three patients presented with evident hematological signs of TMA and AKI, and other aHUS triggering or explanatory events were absent. After eculizumab treatment, kidney function fully recovered in 2/3 patients. In addition, we describe two patients with dubious aHUS relapse after COVID-19 vaccination. To assess the risks of vaccination, we retrospectively evaluated 29 aHUS patients (n=8 with native kidneys) without complement-inhibitory treatment, who received a total of 73 COVID-19 vaccinations. None developed aHUS relapse after vaccination. Conclusion In conclusion, aHUS should be included in the differential diagnosis of patients with vaccine-induced thrombocytopenia, especially if co-occuring with mechanical hemolytic anemia (MAHA) and acute kidney injury (AKI). Still, the overall risk is limited and we clearly advise continuation of COVID-19 vaccination in patients with a previous episode of aHUS, yet conditional upon clear patient instruction on how to recognize symptoms of recurrence. At last, we suggest monitoring serum creatinine (sCr), proteinuria, MAHA parameters, and blood pressure days after vaccination.